A new species of Enchytraeus (Enchytraeidae, Clitellata) from sewage sludge of a plum processing plant in Japan - Torii, Takaaki; Akagi, Tomohiro; Uchino, Toru; Kobayashi, Tohru (Zootaxa, 2023)
Enchytraeus ohtakai sp. nov. (Enchytraeidae, Clitellata, Oligochaeta) was discovered in the organic matter of a wastewater treatment facility of a plums processing plant in Honshu, Japan. The wastewater is characterized by high organic matter content and low salt concentration. Morphological analysis and DNA-sequencing of a fragment of the COI barcoding gene show that the new species belongs to the E. albidus species group. Within this group it differs in: vasa deferentia restricted to XII, preclitellar bundles with mostly three chaetae, postclitellar bundles with two or three, dorsal blood vessel from XII or XIII, spermathecal ectal duct completely glandular. spermatheca with a large diverticulum, accessory sexual glands present in XII, clitellum ventrally almost absent. The individual gene trees of COI analysis recovered this new species as a monophyletic group within the genus Enchytraeus, closely related to E. albidus species group.